Challenges of the disclosure of artificial intelligence in Spanish cybermedia - de Lara, Alicia (2022)
The Digital Frontiers 2019 study, based on a survey of 1500 people, indicates that 62 % of the population consulted does not know what artificial intelligence (AI) is. Specifically, 60 % of respondents believe that AI is a robot. Given the importance of the media for scientific dissemination —according to a 2020 survey by the Spanish Science and Technology Foundation (FECYT), 61 % of Spaniards learn about science through digital media and social networks— we propose to analyze to what extent the contents of Spanish media on AI-related issues are rigorous, comprehensible and adequately explain the technological concepts. Methodologically, the study involves a content analysis of twenty news items published by Spanish-speaking digital media that include the term “artificial intelligence” and consulting ten press professionals about the dissemination of AI. The results indicate that in Spain, media coverage about AI and associated concepts shows an absence of easily comprehensible language for a wide and varied audience, a lack of connection with people’s daily lives, and a lack of depth in its approach to the subject.